Optimalisasi Minat Baca Anak Desa Medalsari di Masa Pandemi melalui Storytelling - Ari Fajria Novari; Fadhila Malasari Ardini; Heva Rostiana; Meliyawati Meliyawati; Mualwi Widiatmoko; Nur Azmi Rohimajaya; Rizdki Elang Gumelar; Sopyan Sauri (Universitas Mathla'ul Anwar Banten, 2020)
OPTIMIZING READING INTEREST IN CHILDREN OF MEDALSARI VILLAGE DURING THE PANDEMIC THROUGH STORYTELLING. This study aims to (1) Attach the implementation reading method to storytelling students’ interesting in reading at Desa Medalsari when pandemic era, (2) attach to happiness, joy and comfort in fostering reader and listener when reading the book and storytelling. The type of research used is qualitative research with a qualitative descriptive research design. This research uses interview, observation and documentation. The object of research is elementary students to leaving at Desa Medalsari. The research showed that students is very interesting and admit that grow up storytelling to help reading interest. The results showed that: (1) the goal of storytelling to make easier the students got the information from the speaker how to read a book from storytelling well. (2) Factors supporting the implementation of reading angles include: the role of the parents who do not provide reading habit, students are not fluent in reading, damaged book. (3) The advantages are the children get the experience of the interesting story. (4) The children will know books and start loving to read books.